Disruption of ubiquitin specific protease 26 gene causes male subfertility associated with spermatogenesis defects in mice†. Issue 4 (25th April 2019) - Tian, Hong; Huo, Yongwei; Zhang, Jie; Ding, Shangshu; Wang, Zhiyong; Li, Hecheng; Wang, Lirong; Lu, Ming; Liu, Sen; Qiu, Shudong; Zhang, Qiuyang
Abstract: Ubiquitin-specific protease 26 ( USP26 ) is an X-linked gene exclusively expressed in the testis and codes for the USP26, a peptidase enzyme that belongs to the deubiquitinating enzyme family. Recent studies have indicated that mutations in USP26 affect spermatogenesis and are associated with male infertility in humans and mice. However, the exact role of USP26 in spermatogenesis and how it affects male reproduction remains unknown. In this study, we generated a conventional Usp26 knockout mouse model and found that deletion of Usp26 in male mice ( Usp26 −/Y ) leads to significantly reduced pup numbers per litter and significantly increased intervals between two consecutive offspring. We also found that the serum follicle stimulating hormone and testosterone levels of adult Usp26 −/Y mice were significantly decreased compared to those of Usp26 +/Y mice. Histological examination results showed that Usp26 −/Y mice had significantly increased percentage of abnormal seminiferous tubules at different ages. Flow cytometry results exhibited that Usp26 −/Y mice had significantly reduced percentage of mature haploid cells in the testes compared to Usp26 +/Y mice. Sperm counts in epididymis were also significantly declined in Usp26 −/Y mice compared to those in Usp26 +/Y mice. Immunohistochemistry and immunofluorescence staining and immunoprecipitation analysis results showed that USP26 and androgen receptor were co-localized in mouse testicular cells at different ages and they both had physiological interactions. All these results demonstrated that the loss of Usp26 affects spermatogenesis and hormone secretion and causes male subfertility. Our study also provides the evidence on the interactions between USP26 and androgen receptor in mouse testis, whereby pointing to a potential mechanism. Abstract : The phenotype of Usp26 knock out in male mice is subfertility, which may be related to the loss of regulation of androgen-AR signaling by USP26 in the testis.